Kajian Model Nonlinear Menggunakan Separable Programming dan Algoritma Genetika pada Lavera Konveksi Padang - Cory Grahayu; Media Rosha (Journal of Mathematics UNP, 2020)
Abstract— Convection is a line of business in the finished clothing section that producess on a large scale or in massive. In the production process, in general the working of convection are not based on customer orders, but based on a standard size. Lavera convection is one of the famous convection in the city of Padang that has obstacles in controlling orders. The purpose of this study is to determine the shape of nonlinear models from optimization of production costs in Lavera Convection using Separable Programming and Genetic Algorithms. The type of research is applied research with secondary data type. The method of data collection was carried out by researchers to the Lavera Convection in Padang and followed by data collection. Separable Programming Method is a method for transforming nonlinear objective functions into linear objective function. By completing the schedulling model using the Genetic Algorithm, the result is the minimum production cost incrured is Rp. 65.223.468, 43 with 540 long-sleeved shirth, 540 collared shirts, 360 T-shirts, 540 training pants.Keywords—optimization, production, nonlinear programming, separable programming, geneticalgorithms